Marriage contract in Ukraine: the practical implementation - Білоусов, Віталій Миколайович; Дмитришина, Валентина Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article deals with the peculiarities of the marriage contract and its practical implementation in our country. The authors define the legal nature of the marriage contract, its practical significance, formulate the main drawbacks and problems and offer solutions. Marriage contract is a civil transaction, based on the agreement of a fiancé and a fiancée or married spouses regarding the establishment of property rights and responsibilities of spouses during the period of marriage and its annulment. Unfortunately, our mentality makes the majority of our citizens believe that a marriage contract is an expression of mistrust and find no objective reasons for entering it, and therefore they do not know what it is actually needed for. In Ukraine, a marriage contract is very rare, it is rather an exception. The most common reason for signing such an agreement is a difference between partners in the status of property, and also the lack of understanding of the necessity of this agreement. In Ukraine, the marriage contract did not get great implementation because the main feature of the Slavic soul is generosity and openness. Unmarried couples are not used to miserly pragmatism, and therefore they do not want to talk about anything practical on an exciting wedding eve. There is a small number of marriage contracts in Ukraine. Low public awareness of its existence and functions and the fact that today not all Ukrainians realize its concept are the main reasons of it. It should be mentioned that the marriage contract is intended to strengthen the family institution, allowing take into account the interests of each spouse better and to reduce the number of arguments and conflicts between them, but even if the feelings are over and, in case of divorce and division of property it can only facilitate the divorce, that is to solve everything in a civilized manner.